Risk Assessment of Noise-induced Hearing Loss Among Workers with Occupational Noise Exposure in University Hospitals - Thanomwong, Tanachot; Aekplakorn, Wichai; Bumrungwech, Piyatad; Phaipayom, Nattida; Buachum, Asadavudh; Monklang, Wiyachatr; Chumsunthorn, Nattacha; Dumavibhat, Narongpon; Wongrathanandha, Chathaya (Biomedical Sciences and Clinical Medicine, 2025)
Objective Occupational noise-induced hearing loss (ONIHL) is preva-lent among supporting healthcare workers in a hospital setting. The risk assessment of ONIHL using a risk matrix could be beneficial, particularly in settings with limited resources; however, it has rarely been applied, and no previous studies have evaluated its accuracy compared to audiogram results. This study aimed to develop a system to evaluate the accuracy of a risk matrix score as a screening tool for the risk of ONIHL. Methods This retrospective cohort study included hospital workers exposed to high workplace noise levels in Ramathibodi Hospital and Siriraj Hospital between 2016 and 2023. The noise levels were monitored in the workplaces, and workers’ annual audiograms were obtained and interpreted. The risk matrix score was developed by multiplying the numerical value of each domain in the risk matrix (probability - P, consequences - C, and exposure time - E), resulting in a score range of 1 to 125. The accuracy of the risk scores for predicting ONIHL was evaluated using the ROC curve. The optimal cut-off value for the risk scores was determined based on sensitivity and specificity, and the scores were classified into five risk levels (R). Results A total of 239 workers were included in the study (45.6% male and 54.4% female), 38.5% of whom were diagnosed with ONIHL. For noise exposure level (P), most workers (70.7%) were exposed to occupational noise levels less than 80 dBA as an 8-hour time-weighted average (level 1). Regarding Consequences (C), the majority (38.5%) experienced moderate health effects from noise exposure (level 3). For exposure time (E), most workers (32.2%) had a job duration of 20 years or more (level 5). In terms of risk categories (R), most workers (40.2%) were in the moderate risk category (level 3), followed by 26.8% in the acceptable risk category (level 1), 20.5% in the low-risk category (level 2) and 12.6% in the high-risk category (level 4). The area under the curve (AUC) of the risk score for predicting ONIHL was 0.667. At a score of 8, the sensitivity and specificity for ONIHL were 65.2% and 55.1%, respectively. Conclusions The risk matrix can moderately predict ONIHL. It should be employed to screen and prioritize high-risk workers for audiometry in settings with limited resources to promote early detection of ONIHL and further noise control.